‘Quo Vadis’ Practical Theology? - Nell, Ian (Scriptura, 2009)
In order to ask the question about the future of a discipline, one must realise where one comes from. This article seeks to answer the "quo vadis" question in conversation with some perspectives offered by the sixteenth century Reformer John Calvin. It is argued that Calvin lived in a century that scholars regard as one of the golden periods in which the world of the arts and theatre flourished. Hence Calvin’s age was characterised by a dramatic vision of human existence and such a vision also had an impact on his own theological thinking. Against this backdrop, the article engages the question of the future of Practical Theology by proposing a theodramatic approach in which the possibilities that the notion of "re-dramatisation" holds, come to the fore.